Safety in student residences matters! - Gopal, N.; van Niekerk, C. (South African Journal of Higher Education, 2018)
Despite a national call for “The provision of accessible, decent, safe and academically conducive student accommodation (Nzimande, 2011) safety in student accommodation in South Africa remains a serious challenge. Against the backdrop of the provision of safe student accommodation, this study, through a qualitative research design, examined residence students’ experiences of safety and security in student accommodation (residences). Through narrative enquiry the study-generated data from purposively sampled male and female residence students representing undergraduate and postgraduate students. The data points to fears and anxieties of students living in residences enabled by a vulnerable (unsafe) residence environment.